New Report on Understanding the Well-Being of LGBTQI+ Populations. Issue 2 (March 2021) - Simpson, Kathleen Rice
Abstract : In October 2020, the National Academies of Sciences, Engineering, and Medicine (NASEM, 2020) released a new report on the health and well-being of lesbian, gay, bisexual, transgender, queer or questioning, intersex, non-binary, and gender-nonconforming (LGBTQI+) populations. Maternity, neonatal, and pediatric nurses are encouraged to read the report, be informed, consider the recommendations, and make plans to be a positive force and role-model to make sure all patients get the respectful, gender-affirming care they need and deserve.